ENVIRONMENTAL LEASE SERVICES FOR ECOTOURISM BUSINESS IN CAT BA NATIONAL PARK, VIET NAM - Thi Thu Ha, Tran; Van Dien, Pham (Journal of Forestry Science and Technology, 2016)
The paper addressed on solving a very important issue concerning environmental lease for implementing ecotourism business. The study answered following questions: (i) How are competitive advantages of environmental lease locations? (ii) How much is the price of environmental lease for ecotourism business? And (iii) Which group of environmental lease locations can be formed? Two main methods were applied in the study including willingness to pay (WTP) and fuzzy regression (FR). The results from 22 environmental lease locations in Cat Ba national park, Hai Phong city, Vietnam, with data collected in 2014 showed that, total area for leasing is 413.5 ha including 250.5 ha of forests, 15.4 ha of non-forested land, 38.7 ha of orchard, 5.0 ha of sandy land and 103.9 ha of surface water area. Competitive advantages of environmental lease locations were described by 8 parameters. Price unit for leasing fluctuates from 0.77 to 19.98 million VND per hectare per year. Price unit for leasing is higher than for contracting from 1.3 to 2.5 times. Based on amount of money for leasing environment, locations were divided into four groups. With results have been achieved from the study, the paper contribute to suggesting of enhancing land use value and environment protection effectiveness for Cat Ba national park in Vietnam.